Analysis of the Representation of Religious Moderation Values in Senior High School Islamic Religious Education Textbooks under the Merdeka Curriculum: A Qualitative Study Using Content Analysis - Ritonga, Asnil Aidah; Nurmawati (Jurnal Pendidikan Islam, 2025)
Purpose – This study aims to evaluate the representation and relevance of religious moderation values in Islamic Religious Education (PAI) textbooks for the Senior High School (SMA) level in North Sumatera. The study responds to the discrepancy between national policies emphasizing the importance of moderation and textbook content that does not fully reflect principles of inclusivity, pluralism, and interfaith dialogue. Design/methods/approach – A qualitative approach was employed using the Qualitative Content Analysis (QCA) method on officially sanctioned PAI textbooks based on the Merdeka Curriculum and KMA No. 183 of 2019. The analysis was conducted on narrative content, visuals, learning activities, and other graphic elements. Data coding and interpretation were supported by ATLAS.ti software, with validity ensured through researcher triangulation and analytical auditing. Findings – The results indicate that PAI textbooks generally represent religious moderation values such as tasamuh (tolerance), tawassuth (moderation), and i’tidal (justice). However, values such as muwathanah (national commitment) and musawah(equality) remain underrepresented. Visual aspects and the integration of learning technology are also minimal, and weaknesses were identified in the editing of religious terminology. Research implications – The study's results serve as a foundation for policymakers, textbook authors, and educators to revise instructional materials to be more inclusive in narrative, visual, and digital dimensions. Recommendations are directed toward strengthening the internalization of moderation values through contextual pedagogical approaches and technology integration.